GAMBARAN JUMLAH LEUKOSIT PADA PENDERITA DEMAM TIFOID - ZAITUL WIDAT; ASRI JUMADEWI; SITI HADIJAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Typhoid fever is caused by infection with the bacterium Salmonella typhi which attacks the digestive tract. Clinical symptoms of typhoid fever are characterized by complaints of fever that occur in the afternoon or evening, with a slow and gradual increase in temperature or commonly called step ladder fever. The diagnosis of typhoid fever is in the form of clinical symptoms, physical examination and laboratory examination. One of the laboratory tests by counting the number of leukocytes. The purpose of this study was to describe the number of leukocytes in patients with typhoid fever in dr. Zainoel Abidin. The research method is descriptive with a cross sectional design, which relies on secondary data taken in May 2022, there are as many as 20 respondents who carry out laboratory examinations. The results showed as many as 16 people (80%) with normal leukocyte counts, 3 people (15%), and 1 patient (5%). The average value of the leukocyte count was 8.40 x 103 cells/mm^3 with the lowest value of 3.16 x103 cells/mm^3 and the highest value of 12.90 x 103 cells/mm^3. ABSTRAKDemam tifoid disebabkan oleh infeksi bakteri Salmonella typhi yang menyerang saluran pencernaan. Gejala klinis demam tifoid ditandai dengan adanya keluhan demam yang terjadi pada sore atau malam hari, dengan kenaikan suhu secara lambat serta bertahap atau biasa disebut step ladder fever. Diagnosis penyakit demam tifoid berupa gejala klinis, pemeriksaan fisik dan pemeriksaan laboratorium. Salah satu pemeriksaan laboratorium dengan menghitung jumlah leukosit. Tujuan penelitian ini untuk mengetahui gambaran jumlah leukosit pada penderita demam tifoid di RSUD dr. Zainoel Abidin. Metode penelitian adalah deskriptif dengan desain cross sectional, yang mengandalkan data sekunder yang diambil pada bulan Mei 2022, terdapat sebanyak 20 responden yang melakukan pemeriksaan laboratorium. Hasil penelitian menunjukkan sebanyak 16 orang (80%) dengan jumlah leukosit normal, jumlah leukosit yang meningkat sebanyak 3 orang (15%), dan pasien dengan kadar leukosit menurun sebanyak 1 orang (5%). Nilai rata-rata jumlah leukosit sebesar 8,40 x 103 sel/ dengan nilai terendah 3,16 x103 sel/ dan nilai tertinggi 12,90 x 103 sel/ .